Pengaruh Pemberian Dosis POC Urine Kambing Terhadap Pertumbuhan dan Hasiltanaman Pakchoy (Brassica chinensis L.) - Wibawa Mukti, Denny; Yonny Arita Taher; Dewirman Prima Putra (Jurnal Research Ilmu Pertanian, 2022)
Research on "The Effect of Goat Urine Dosing on Growth and Yield of Pakchoy (Brassica chinensis L.)" has been carried out in the Experimental Garden of the Faculty of Agriculture, Ekasakti University, Padang, which began in July 2019 until September 2019. The aim was to find out and obtain doses The best POC of goat urine on growth and yield of pakchoy (Brassica chinensis L.) plants. This study was arranged in a Completely Randomized Design (CRD) with 6 treatments and 4 replications, all consisting of 24 treatment plots with 5 plants in each plot. The treatment is A = without POC, B = 30 mℓ POC / liter of water per plant, C = 60 mℓ POC / liter of water per plant, D = 90 mℓ POC / liter of water per plant , E = 120 mℓ POC / liter of water per plant, F = 150 mℓ POC / liter of water per plant. By giving 4x the plant-1 (100 mℓ, 200 mℓ, 300 mℓ and 400 mℓ). The parameters observed in this study were plant height, number of leaves, longest leaf length, widest leaf width, and wet weight per plant. Data were analyzed statistically by the F test, if F count > F table 5%, then further testing with Duncan's New Multiple Range Test (DNMRT) at 5% significance level. The best yield for growth and yield of pakchoy plants is a dose of 90 mℓ / ℓ water plant-1. Based on the results it can be recommended for the administration of goat urine liquid organic fertilizer to plants of pakchoy (Brassica chinensis L.) at a dose of 90 mℓ / ℓ water per plant.